Mufradāt al-Kitāb al-Arabiyyah Li an-Najāh ‘Inda Naẓariyyah ‘Abd ar-Rahmān Ibn Ibrāhim al-Fauzān - Nuruddin, Ahmad; Rosyidi, Abdul Wahab; Sodik, Achmad Ja’far; Rufaiqoh, Elok (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2024)
Purpose– Vocabulary is one of the main keys to being able to learn a foreign language because without vocabulary learning a foreign language will be very difficult to implement. Among the learning resources are books that also study vocabulary, with various presentations. However, the system for presenting vocabulary in books still requires a deeper review in terms of the concept of presentation. Design/Methodology/Approach– Through mixed methods based on literature studies, this article reveals how the concept of presenting vocabulary in Abdur Rahman bin Ibrahim Al-Fauzan's perspective book. The data is processed from the book "Al-'Arabiyyah li Al-Najah Book 1" using an integrated reading technique which is then linked to the concept of Ibrahim Al-Fauzan as well as facts on the presentation of vocabulary in other books from various sources of articles or news. Findings– This article produces 7 principles for presenting vocabulary in books, namely: 1) amount 2) practice questions 3) level of difficulty 4) reinforcement 5) structure 6) purpose and method of introduction 7) topic selection. Some of these principles are accompanied by descriptions and facts used in existing books and articles, and this makes an assessment based on the concept of Ibrahim Al-Fauzan with an assessment of the research book "Al-'Arabiyyah li Al-Najah Book 1" which is 85.7. These findings can form the basis for the concept of writing vocabulary in books as a source of student teaching as well as efforts to develop textbooks. Research Limitation– The limitations of this study are focused only on vocabulary in a teaching material, to find out how the quality of vocabulary in the book "Al-'Arabiyyah li Al-Najah Book 1" using the perspective of Ibrahim Al-Fauzan's concept. This study does not discuss the contents of the book as a whole, but only on the form of vocabulary that will be studied in depth.